A Preview on the Conceptualization of Contemporary Knowledge from Islamic Knowledge Management Perspective - Muhamadul Bakir Hj. Yaakub; Khatijah Othman; Ahmad F. Yousif (Faculty of Business and Management and UiTM Press, Universiti Teknologi MARA, 2024)
Vol 3 No 1